Synthesis of MIL-53(Fe) Metal-Organic Framework Material and Its Application as a Catalyst for Fenton-Type Oxidation of Organic Pollutants - Pham Dinh Du; Pham Ngoc Hoai (Advances in Materials Science and Engineering)
The iron (III) benzene dicarboxylate metal-organic framework material (MIL-53(Fe)) was synthesized with either the solvent-thermal or hydrothermal method under different conditions. The influence of the type of solvents, molar ratio of precursors and solvent, temperature, and reaction time on the structure of MIL-53(Fe) was investigated. The material was characterized by using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HR-TEM), X-ray photoelectron spectroscopy (XPS), and N2 adsorption/desorption isotherm. The MIL-53(Fe) structure formed in N′, N-dimethylformamide (DMF) and methanol (MeOH) but not in water. In DMF, the molar ratio of precursors and solvent, temperature, and reaction time had a significant effect on the crystal structure of MIL-53(Fe). Under optimal conditions, MIL-53(Fe) has high crystallinity and a large specific surface area (SBET = 88.2 m2/g). The obtained MIL-53(Fe) could serve as a potential heterogeneous catalyst to oxidize phenol (PhN), rhodamine B (RhB), and methylene blue (MtB) in the Fenton-like reaction system at the different solution pHs.